Catalysing Actionable Knowledge for Digitalisation in ACP Agribusiness: Core team experience - Pirani, Pier Andrea (Technical Centre for Agricultural and Rural Cooperation, 2018)
Pier Andrea Pirani, one of the facilitators in the core team, shares his experience.